Assessing the safety and use of medicinal herbs during pregnancy: a cross-sectional study in São Paulo, Brazil - Im, Hyea Bin; Ghelman, Ricardo; Portella, Caio Fábio Schlechta; Hwang, Jung Hye; Choi, Dain; Kunwor, Sangita Karki; Moraes, Sandra Dircinha Teixeira de Araújo; Han, Dongwoon (Frontiers in Pharmacology, 2023)
Background: Despite the lack of evidence supporting the safety and clinical efficacy of herbal medicine (HM), its use among pregnant women continues to increase. Given the high prevalence of contraindicated herbs among the pregnant population in Brazil, it is crucial to examine the use of HM and evaluate its safety based on the current scientific literature to ensure that women are using HM appropriately.A cross-sectional study was conducted from October 2022 to January 2023 at a public teaching hospital in São Paulo, Brazil. A total of 333 postpartum women in the postnatal wards and postnatal clinic were interviewed using a semi-structured questionnaire. The survey instrument consisted of 51 items covering the use of HM during pregnancy, sociodemographic and health-related characteristics, COVID-19 experiences, and pregnancy outcomes. For data analysis, chi-square and multivariate logistic regression were conducted using SPSS ver. 26.0.Results: Approximately 20% of respondents reported using HM during their most recent pregnancy, with a higher use observed among women from ethnic minority groups and those with prior HM experience. Among the 20 medicinal herbs identified, 40% were found to be contraindicated or recommended for use with caution during pregnancy. However, only half of the women discussed their HM use with obstetric care providers.This study emphasizes the continued public health concern regarding the use of contraindicated or potentially harmful HM among pregnant women in Brazil, highlighting the need for sustained efforts to reduce the risk of inappropriate HM use. By updating antenatal care guidelines based on the latest scientific evidence, healthcare providers can make informed clinical decisions and effectively monitor pregnant women's HM use, ultimately promoting safer and more effective healthcare practices.